Estimation of aerodynamic parameters of a hybrid airship - Amelda Dianne binti Andan (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The aerodynamic parameters of a conventional wingless airship and a preliminary winged-hull airship design are investigated. The research methodology involved the use of numerical simulation and wind tunnel testing. The aerodynamic parameters of the designs are first computed using a commercial CFD code. The force and moment coefficients are then measured on a scaled model in the IIUM low speed wind tunnel. The experimental results were used to validate the reliability of CFD results in order to predict the full scale airship models. It is found out that the experimental results generally agree with the CFD predicted data. Addition of a wing to conventional airship increases the lift substantially with a reasonable increase in drag. In general, winged airship has three times the lifting force at positive angle of attack compare to wingless airship whereas the drag increases in the range of 16% to 58%. The conventional airship and the hybrid airship were found to be statically stable for both longitudinal and directional stability motions; however, they have poor rolling stability. Winged airship has slightly more stable longitudinal motion than wingless airship. The wingless airship has better directional stability than the winged airship. However, the wings contribution to directional stability is found to be negligible. The wingless airship only possesses static rolling stability at the range of yaw angle of -5° to 5°. On the contrary, the winged airship does not possess rolling stability at all. CFD simulations show that modifications to the wing placement and its dihedral have strong positive effect on the rolling stability. Raising the wings on the center of gravity and introducing dihedral angle of 5° stabilize the rolling motion of the winged airship.